Is arrest for prohibited drug use a prelude to more serious offending? - Wan, Wai-Yin (Journal of criminology, 2022)
Although they constitute a significant fraction of the workload of most courts, very little research has been conducted on the criminal careers of those who commit minor offences. Such research is important for both theoretical and practical reasons. It is of theoretical importance because the criminal careers of those who commit minor offences may differ significantly from those who commit serious offences. It is of practical importance because the assumed rate of re-offending among minor offenders has a bearing on both the sentence imposed and the question of whether some offences should be decriminalised. Use or possession of a prohibited drug is a common minor offence ? and one that many have argued should be decriminalised. Little is known, however, about the criminal careers of those convicted of this offence. We do not know what proportion are rearrested, what further offences (if any) they commit, or what factors affect the rate of offending among those who do have further contact with the criminal justice system. To answer these questions, we examined a cohort of 13,953 people whose first proven offence was for the use or possession of a prohibited drug and examined their criminal careers over an average period of 4.4 years (sd.?=?3.4 years, range?=?20.8 years). The majority (73%) had no further contact with the NSW criminal justice system. The most common offence among those who did re-offend was another drug possession offence. Significantly higher risks of re-offending were found among those living in areas in the lowest quartile of disadvantage and among those found in possession of cannabis. The implications of these findings are discussed.